Merry Christmas, Mouse! - Numeroff, Laura Joffe; Bond, Felicia (New York : Laura Geringer Books, 2007)
"Join Mouse from If You Give a Mouse a Cookie as he decorates his Christmas tree in a holiday counting adventure."--p. [4] of cover.
Cover title.
On board pages.
"An if you give... book"--Cover.
All ages.
Keywords: Mice -- Juvenile fiction; Christmas -- Fiction; Counting -- Fiction